Documenting mobility in the Japanese empire and beyond - Yamamoto, Takahiro (Palgrave Macmillan, 2022)
Intro -- Acknowledgements -- Contents -- Notes on Contributors -- List of Figures -- Introduction: The Imperial Paperchase -- Identifying Japanese on the Move -- Outline of the Book -- References -- Laws and Transgressions -- Legislating Global Mobility in Japan: Opening the Pacific, Treaty Ports, and Asian Exclusion -- Looking Backward from 1874: Legislating Access and Restriction -- The First Round of Treaties in Global Context, 1853-1856 -- The Second Round of Treaties in Global Context, 1858-1871 -- The Colima's Arrival at Yokohama in 1874: Regulating Access
Includes index
Keywords: Japan -- History -- 20th century; Japan -- Emigration and immigration -- History -- 20th century; Japan; Electronic books; Aufsatzsammlung